Gas Chromatography-Mass Spectrometry profiling, and evaluation of antioxidant and antibacterial activity of Albizia spp. - Arindam Ghosh; SOUMYA MAJUMDER; SUMEDHA SAHA; SAHADEB SARKAR; MALAY BHATTACHARYA (Smujo International, 2021)
Abstract. Ghosh A, Majumder S, Saha S, Sarkar S, Bhattacharya M. 2021. Gas Chromatography-Mass Spectrometry profiling and evaluation of antioxidant and antibacterial activity of Albizia spp. Nusantara Bioscience 13: 177-184. Plant resources have been utilized for human welfare since ancient times. Most of the pharmaceutical industry relies on bioactive molecules from plant resources. This research was carried out to investigate the antioxidant and antibacterial activities of Albizia spp. DPPH assay was conducted to investigate the antioxidant activity, and a well-diffusion test by pour plate method was followed for antibacterial assay. Antioxidant activity confirmed that the leaf extracts with chemical contents having solubility in polar solvents showed high free radical scavenging activity. Bark extracts' free radical scavenging activities were lower than the leaf extracts. Leaf extracts of Albizia procera showed the highest scavenging activity (94.77% or 100.66 µg AE/ ml), followed by Albizia odoratissima (93.52% or 99.23µg AE/ ml), Albizia lebbeck (91.68% or 97.13 µg AE/ ml) and Albizia chinensis (89.91% or 95.11 µg AE/ ml). GC-MS analysis of leaf and bark extracts revealed that 15 compounds had been reported to have antioxidant activities such as beta-amyrin, phytol, squalene, and vitamin E, and 31 compounds had been reported to have antimicrobial, antibacterial, antifungal, and antiviral activity. The antibacterial activities of leaf and bark extracts of four Albizia species showed that leaf extracts of Albizia spp. showed better antibacterial activity compared to bark samples which were compatible with the results from GC-MS analysis.